Chromosome-scale assembly and quantitative trait locus mapping for major economic traits of the Culter alburnus genome using Illumina and PacBio sequencing with Hi-C mapping information - Liu, Shili; Zheng, Jianbo; Li, Fei; Chi, Meili; Cheng, Shun; Jiang, Wenping; Liu, Yinuo; Gu, Zhimin; Zhao, Jinliang (Frontiers in Genetics, 2023)
Culter alburnus is economically important freshwater fish with high nutritional value. However, its potential genetic advantages have not been fully exploited. Twenty-four peudochromosomes were anchored by 914.74 Mb of the C. alburnus sequences. De novo sequencing identified 31,279 protein-coding genes with an average gene length of 8507.7 bp and average CDS length of 1115.23 bp. In addition, a high-density genetic linkage map consisting of 24 linkage groups was constructed based on 353,532 high-quality SNPs and 4,710 bin markers. A total of 28 QTLs corresponding to 11 genes, 26 QTLs corresponding to 11 genes and 12 QTLs corresponding to 5 genes were identified for sex, intermuscular spinenumber and body weight traits. In this study, we assembled accurate and nearly complete genomes of C. alburnus by combining Illumina, PacBio and high-throughput Chromosome conformation capture (Hi-C) technologies. In addition, we identified the quantitative trait locus (QTLs) explaining variances in intermuscular spinenumber, body weight and sex differences in the C. alburnus. These genetic markers or candidate genes associated with growth traits provide a basis for marker-assisted selection in the C. alburnus.